ETIOLOGY AND INNOVATIVE APPROACH TO THE TREATMENT OF ACUTE AND CHRONIC INFECTIOUS INFLAMMATORY DISEASES OF BRONCHOPULMONARY SYSTEM IN CHILDREN - Ye.V. Sereda; L.K. Katosova (Вопросы современной педиатрии)
The article presents modern data on etiology of acute and chronic inflammatory diseases of airways in children. Special attention is given to the treatment with oral antibiotics and to the meaning of these drugs. Authors give a literature review of biological, pharmacokinetic and anti-microbal activities of macrolides and particularly azithromycin. Detailed characteristics of effects of macrolide antibiotic azithromycin and tactics of its administration for the treatment of airways diseases in children are presented. The article describes nonantibacterial effects of azithromycin: anti-inflammatory, immunomodulatory and mucoregulatory ones. New activities of azithromycin are structural and functional defence of respiratory epithelium and ability to prevent adhesia of microorganisms. These properties of a drug widen the indications of its administration. The reasonability of its use for treatment of out-of-hospital pneumonias including atypical ones (mycoplasmal and chlamidia pneumonias) and in patients with exacerbations of chronic inflammatory bronchopulmonary diseases was show.Key words: children, acute and chronic respiratory diseases, pneumococcus, hemophilus influenza, azithromycin.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (3): 124–130)